#TITLE_ALTERNATIVE# - ABDUL MATIN (NIM 13205160); Pembimbing: Dr. Ir. Muhammad Nurdin dan Ir.Nanang Haryanto, MT., TOTOH
Increasing of electric demand on the system will cause a system reconfiguration and it will change the reliability level at each substation. To get the optimal reliability level, we must spend the investation to build up generators and transmission lines. The final project deals with a mechanism of investation cost allocation to all of party in the system. The method that will use to allocate the investation cost is based on the Cooperative Game Theory. In this theory, one party/player will make a cooperation (coalition) with other party/player to get cheaper investation and operation cost. The theory application will be analized in Garver System. The result of research bring up the formation step of bilateral coalition in order to make a big coalition (Grand Coalition). To give a description about players contribution in the coalition, this final project show the investation cost allocation and operational profit obtained by each player in coalition.